Court of the Universe - Bedford, Thomas A.:::::::::
View of the Arch of the Rising Sun and the Fountain of the Setting Sun, foreground, and the Fountain of the Rising Sun, background. Also view of the dome of the Palace of Agriculture on right side of photograph.